Downregulation of TCF1 in HIV Infection Impairs T-cell Proliferative Capacity by Disrupting Mitochondrial Function - Cai, Hong-Jiao; Shi, Jue; Yin, Lin-Bo; Zheng, Jie-Fu; Fu, Ya-Jing; Jiang, Yong-Jun; Shang, Hong; Zhang, Zi-Ning (Frontiers in Microbiology, 2022)
Background Despite the benefits of antiretroviral therapy (ART) for people with HIV, T-cell dysfunction cannot be fully restored. Metabolic dysregulation is associated with dysfunction of HIV-1-specific T-cells. Exploration of the factors regulating metabolic fitness can help reverse T-cell dysfunction and provide new insights into the underlying mechanism. Methods In this study, HIV-infected individuals and HIV-negative control individuals (NCs) were enrolled. T-cell factor (TCF)1 expression in cells was determined by quantitative reverse-transcriptase polymerase chain reaction and flow cytometry. Relevant microarray data from the GEO database were analyzed to explore the underlying mechanism. The effects of TCF1 on T-cell function and metabolic function were assessed in vitro. Results TCF7 mRNA expression in peripheral blood mononuclear cells was downregulated in rapid progressors compared with long-term non-progressors individuals and NCs. TCF1 expression on CD4+ and CD8+ T-cells was downregulated in treatment-naïve HIV-infected individuals compared with NCs. Interleukin (IL)2 production and proliferative capacity were impaired in TCF1 knockdown T-cells. Moreover, glycolytic capacity and mitochondrial respiratory function were decreased in TCF1 knockdown T-cells, and depolarized mitochondria were increased in TCF1 knockdown T-cells. Conclusion Downregulation of TCF1 in HIV infection impairs T-cell proliferative capacity by disrupting mitochondrial function. These findings highlight the metabolic regulation as a pivotal mechanism of TCF1 in the regulation of T-cell dysfunction.